MEMAHAMI ESENSI PENGALAMAN STEREOTIPISASI WANITA DI DUNIA PUBLIC RELATIONS - Chairunnisa, Chairunnisa; Sunarto, Sunarto; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Gender inequality in Indonesia still frequently occurs, especially in the field of Public Relations, which is often seen as a feminine industry in terms of gender issues. According to Deborah (2017), in her research examining the relationship between public relations practitioners and feminist theory, it is stated that marketing, advertising, and public relations attract more female participants compared to males. This statement is also supported by data from the PRSA (Public Relations Society of America), where 70% of registered practitioners are women (Wrigley, 1999). This research aims to understand the essence of women’s stereotyping experiences in the workplace, particularly in hotels, an industry that often requires PR as a long-term investment for the company. The research uses a critical paradigm with a critical phenomenology approach. The theory applied is the Standpoint Feminist Liberal Theory. The data collection method used in this research involved in-depth interviews with two female employees as informants. The results of the study show that female employees in two hotel companies experience forms of stereotyping, such as negative labeling, special treatment, and specific expectations directed at female PR employees. Although they experienced different forms of stereotyping, the informants viewed them in different ways. The first informant considered it as a challenge or a job risk that every female PR employee must face, while the second informant saw it as a shortcoming in the PR world that she needs to overcome as a PR leader.